Assessing and treating conversations with partners in Parkinson’s disease: A scoping review of the evidence - Thilakaratne, Ramishka; Loftus, Andrea; Cocks, Naomi (2021)
Purpose: This is a scoping review of the methods used in published research to assess conversations and the interventions used to treat conversations between people with Parkinson’s disease and their partners. Communication partners were defined as significant others or next-of-kin. The aims were to describe the assessment methods and interventions used, and to identify gaps in the literature.